4Y+119=22
3X*189=5
8Z/6=458
3X+77=59
4Y-6985=81
87X*13=5
7Z/93=41
15X+863-65X=54
58Y*55=27489
z*(z-3)=4
The roots of the equation x2 = are .
2. The general form of the equation (x+1)2-2(x-1)2 = 6x-5 is .
3. One of the roots of the quadratic equation x2 + mx + 3 = 0 with respect to x is 1. The value of m is .
4. It is known that the quadratic trinomial x2+2mx+4-m2 is a perfect square, then m= .
5. It is known that +(b-1)2=0 and the equation kx2+ax+b=0 has two unequal real roots when k is .
6. The equation mx2-2x+1=0 has only one real root with respect to x. Then m= .
7. Write the quadratic equation with one root of 1 and another root satisfying -1<x<1 is .
8. The equation x2-(2m2+m-6)x-m=0 with two roots opposite to each other is m= .
9, It is known that the two roots of the quadratic equation (a-1)x2+x+a2-1=0 are x1,x2 and x1+x2= , then x1,x2= .
II. Multiple choice questions: (3'×8 = 24')
11. The equation (m+1)x2+2mx-3=0 about x is a quadratic equation, then the value of m is ( )
A, any real number B, m≠1 C, m≠ -1 D, m>-1
12. The following are fill-in-the-blank questions answered by a student on a math quiz, of which the correct answer is ( )
A. If x2=4, then x=2 B. If 3x2=bx, then x=2
C. One root of x2+x-k=0 is 1 , then k=2 D. If the value of the partition is zero, then x=2
13, the case of the roots of the equation (x+3)(x-3)=4 is ( )
A, there are no real roots B, there are two unequal roots of the real numbers C, the two roots are inverses of each other D, the two roots are opposites of each other
14, a quadratic equation x2 -3x-1=0 and x2+4x+3=0 has a sum of all real roots equal to ( ).
A, -1 B, -4 C, 4 D, 3
15, the known equation ( ) 2 - 5 ( ) + 6 = 0, set = y can be changed to ( ).
A, y2+5y+6=0 B, y2-5y+6=0 C, y2+5y-6=0 D, y2-5y-6=0
16, a supermarket's turnover in January was 1 million yuan, and in the first quarter The turnover ***8 million yuan, if the average monthly growth rate of x, the equation should be ( )
A, 100(1 + x)2 = 800 B, 100 + 100 × 2x = 800 C, 100 + 100 × 3x = 800 D, 100 [1 + (1 + x) + (1 + x)2] = 800
17, known The quadratic equation 2x2-3x+3=0, then ( )
A, the sum of the two roots is -1.5 B, the difference of the two roots is -1.5 C, the product of the two roots is -1.5 D, there are no real roots
18, it is known that a2+a2 -1 = 0, b2 + b2-1 = 0 and a ≠ b, then ab + a + b = ( )
A, 2 B, -2 C, -1 D, 0
Three, solve the following equations:
19, (x -2)2-3 = 0
20, x(8 + x) = 16
21, (2x-3)2-2(2x-3)-3 = 0 p>
22, 2x2 - 5x + 1 = 0
/question/30122056.html?si=3
This is what others have answered, it's pretty complete